Auschwitz : [the story of a Nazi death camp] - Lawton, Clive A. 1951- (Candlewick Press, 2002)
A description of what happened at Auschwitz, a concentration camp in Poland used during World War II by the Nazis to gather and murder many people, mostly Jews